Yield and Quality of New Strawberry Advanced Breeding Selections and Commercial Cultivars, Grown Under Warm-Temperate Climatic Conditions - Gessica Altieri; Daniele Curcio; Alessandra Lepore; Elèna Grobler; Angela Maffia; Nicola Gargano; Antonio Tedesco; Maria Luisa Graziano; Pierluigi Mazzei; Franco Capocasa; Bruno Mezzetti; Giuseppe Celano (Agriculture, 2025)
Climate change challenges existing strawberry cultivars, requiring adaptation and the introduction of new varieties better suited to new climate conditions. This research evaluated the response over time of new advanced breeding selections (AN15,07,53, AN16,53,54 and AN12,44,60) derived from intraspecific crosses, proposed for the Mediterranean environment and organic greenhouse cultivation, by comparing plant yield and fruit quality at each harvest stage against five commercial strawberry cultivars (Dina, Arwen, Melissa, Marimbella, and Elide). Results showed that Dina, AN15,07,53, and AN16,53,54 had higher levels of soluble sugars, organic acids, and anthocyanins than the other cultivars evaluated. In addition, AN16,53,54 showed anticipated peak production and plant yield similar to that of commercial cultivars. Elide showed on average the highest total yield (632 g plant−1), while Dina, AN15,07,53 and AN12,44,60 showed lower yields. The lowest and highest percentages of discarded fruits were recorded in Arwen (10%) and AN 12,44,60 (27.7%), respectively. Two genotypes, AN16,53,54 and AN15,07,53 are susceptible to further evaluation; AN16,53,54 showed appropriate features for organic systems management. An important feature related to the environmental conditions of the Mediterranean area is the precocity of production, combined with good quality properties. The genotype AN15,07,53 derived from two parents with high and low chilling requirements, would need to be evaluated for its performance under very different climatic conditions.